Revisiting the immunopathology of congenital disorders of glycosylation: an updated review - Pascoal, Carlota; Francisco, Rita; Mexia, Patrícia; Pereira, Beatriz Luís; Granjo, Pedro; Coelho, Helena; Barbosa, Mariana; dos Reis Ferreira, Vanessa; Videira, Paula Alexandra (Frontiers in Immunology, 2024)
Glycosylation is a critical post-translational modification that plays a pivotal role in several biological processes, such as the immune response. Alterations in glycosylation can modulate the course of various pathologies, such as the case of congenital disorders of glycosylation (CDG), a group of more than 160 rare and complex genetic diseases. Although the link between glycosylation and immune disfunction has already been recognized, the immune involvement in most CDG remains largely unexplored and poorly understood. In this study, we provide an update on the immune dysfunction and clinical manifestations of the 12 CDG with major immune involvement, organized into 6 categories of inborn errors of immunity according to the International Union of Immunological Societies (IUIS). The immune involvement in phosphomannomutase 2 (PMM2)-CDG -the most frequent CDG -was comprehensively reviewed, highlighting a higher prevalence of immune issues during infancy and childhood and in R141H-bearing genotypes. Finally, using PMM2-CDG as a model, we point to links between abnormal glycosylation patterns in host cells and possibly favored interactions with microorganisms that may explain the higher susceptibility to infection. Further characterizing immunopathology and unusual host-pathogen adhesion in CDG can not only improve immunological standards of care but also pave the way for innovative preventive measures and targeted glycan-based therapies that may improve quality of life for people living with CDG.